Comparing one-way sideswipe crash treatments on curved multilane roads: Estimating accident modification factor for partial physical lane separation treatment - Al-Shaar, Walid (International Journal of Innovative Research and Scientific Studies, 2025)
Road crashes are more prevalent on curved road sections compared to straight, multilane, one-directional sections. This study focuses on a driving behavior known as "curve-cutting," a major cause of sideswipe crashes. To address this issue, the study evaluates the perceived effectiveness of partial physical lane separation treatments (PPLSTs) within the road pavement layer in Lebanon. Three types of PPLSTs were introduced: raised pavement markers (RPM), transverse rumble strips (TRS), and scratched asphalt surfaces (SAS). A questionnaire survey assessed the perceived effectiveness of PPLSTs on driving behavior and identified the main causes of crashes on curved road sections. Results indicate that combined high-speed and reduced-attention driving, followed by high-speed driving alone, are the primary causes of crashes. Most respondents perceive TRS as the most effective solution, followed by SAS. These findings are used in a multicriteria decision analysis to preliminarily estimate the accident modification factors (AMF) for the PPLSTs. The preliminary estimated AMF values for TRS and SAS are less than 0.94 and 0.67, respectively. The results are crucial for developing targeted road safety measures and policies, providing insights for implementing artificial intelligence algorithms in autonomous vehicles.